Contribution of Zinc Oxide and Halloysite Nanotubes in Epoxy Coating for Corrosion Protection - Yazib, Muhammad Muaz (IRC, 2020)

(untitled)
Corrosion is a major problem which contribute to failure and give impact to the integrity of equipment and pipeline especially in oil and gas industries. Therefore, several methods such as protective coating need to be applied to prevent the corrosion. However, protective coating still have possibilities of being harmed to cracks during its service life. Several methods have been introduced to improve the coating such as addition of nanocomposite materials or nanofillers. Zinc Oxide (ZnO) is an example of nanofillers that widely used in many applications. However, it is not effective to add nanofillers directly into the protective coating. This problem can be overcome by the uses of carrier to encapsulate the nanofillers.